Impact of disruptive technologies on maritime trade and maritime industry : blockchain, 3D printing, e-commerce & battery technology (for harbour craft) - Lam, Jasmine Siu Lee (Nanyang Technological University, 2021)
Disruptive technologies are introducing new threats and opportunities for companies, government bodies, and economies. Understanding the impact of disruptive technologies is a priority for industry leaders and policymakers across all economic sectors. For the maritime sector, the impact of rapid technological change can be categorised into two key areas: i) impact on the maritime industry itself through changing business models driven by technology; ii) impact on maritime trade caused by upstream technological changes in other sectors, e.g. in manufacturing. This report focuses on the following four disruptive technologies and aims to generate new insights on the impact of these technologies on maritime trade and maritime industry: 3D printing, blockchain, e-commerce, and battery technology for harbour craft. The analyses are conducted from different perspectives such as the change of global supply chains, flow of information and finances, physical cargo movement, infrastructure development and environmental impact. Implications are also provided for stakeholders better preparing themselves for future opportunities and challenges.